2006 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--948
|View full text |Cite
|
Sign up to set email alerts
|

Identifying And Investigating Difficult Concepts In Engineering Mechanics And Electric Circuits

Abstract: Indiana University at Bloomington. She is co-principle investigator of three NSF-sponsored projects: Developing an Outcomes Assessment Instrument for Identifying Engineering Student Misconceptions in Thermal and Transport Sciences (DUE -0127806), Center for the Advancement of Engineering Education (ESI-0227558), and Rigorous Research in Engineering Education: Creating a Community of Practice (DUE-0341127). Monica Geist, University of Northern Colorado MONICA R. GEIST is a doctoral student in the Applied Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Findings from studies of the data suggested that civil and mechanical engineering students do not understand accurately the concept of force. In conjunction, their findings indicate that these students view force as a material object 5 .…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…Findings from studies of the data suggested that civil and mechanical engineering students do not understand accurately the concept of force. In conjunction, their findings indicate that these students view force as a material object 5 .…”
Section: Introductionmentioning
confidence: 72%
“…It is not clear if this misconception of force may also impair or limit a student's ability to understand, recall and apply more advanced and related Statics concepts such as FBD and equilibrium to the solution of Statics problems. The study described in this paper re-looks at the data from Streveler and colleagues 4,5 earlier study.…”
mentioning
confidence: 83%
See 3 more Smart Citations